Beyond system logging: human logging for evaluating information visualization - Henry Riche, Nathalie (In BELIV'10 workshop at ACM SIGCHI 2010, 2010)
In this position paper, we propose to investigate novel technologies for evaluating information visualization systems: physiological sensing. We review existing technologies and describe how advances in physiological sensing open a novel perspective for the evaluation of information visualization systems